Characteristics of metachronous gastric neoplasms after curative endoscopic submucosal dissection for early gastric neoplasms - Shan-Shan Xu (Wolters Kluwer, 2021)
Abstract. Background:. With the wide application of endoscopic submucosal dissection (ESD) for early gastric neoplasms, metachronous gastric neoplasms (MGN) have gradually become a concern. This study aimed to analyze the characteristics of MGN and evaluate the treatment and follow-up outcomes of MGN patients. Methods:. A total of 814 patients were retrospectively enrolled. All these patients were treated by ESD for early gastric cancer or gastric dysplasia between November 2006 and September 2019 at The First Medical Center of Chinese People's Liberation Army General Hospital. The risk factors for MGN were analyzed using Cox hazard proportional model. Moreover, the cumulative incidence, the correlation of initial lesions and MGN lesions, and the treatment and follow-up outcomes of MGN patients were analyzed. Results:. A total of 4.5% (37/814) of patients had MGN after curative ESD. The 3-, 5-, and 7-year cumulative incidences of MGN were 3.5%, 5.1%, and 6.9%, respectively, and ultimately reaching a plateau of 11.3% at 99 months after ESD. There was no significant correlation between initial lesions and MGN lesions in terms of gross type (P = 0.178), location (long axis: P = 0.470; short axis: P = 0.125), and histological type (P = 0.832). Cox multivariable analysis found that initial multiplicity was the only independent risk factor of MGN (hazard ratio: 4.3, 95% confidence interval: 2.0–9.4, P < 0.001). Seventy-three percent of patients with MGN were treated by endoscopic resection. During follow-up, two patients with MGN died of gastric cancer with lymph node metastasis. The disease-specific survival rate was significantly lower in patients with MGN than that in patients without MGN (94.6% vs. 99.6%, P = 0.006). Conclusions:. The MGN rate gradually increased with follow-up time within 99 months after curative gastric ESD. Thus, regular and long-term surveillance endoscopy may be helpful, especially for patients with initial multiple neoplasms.